A guide to filtration with string wound cartridges : influence of winding parameters on filtration behaviour of string wound filter cartridges /: influence of winding parameters on filtration behaviour of string wound filter cartridges. (2016) - Kanade, Pragnya M; Bhattacharya, Someshwar S
No abstract available